Safety of indocyanine green use in bariatric and metabolic surgery - Mateusz Wityk; Maciej Bobowicz; Natalia Dowgiałło-Gornowicz (Videosurgery and Other Miniinvasive Techniques, 2025)
Introduction: Intraoperative indocyanine green (ICG) is increasingly used in surgery. In metabolic and bariatric surgery, it allows visualization of the tissues and blood supply to anastomoses in real time.